التفرق الحزبي السياسي بين المسلمين في ماليزيا في ضوء السنة النبوية : دراسة تقويمية - Ahmad Izzuddin bin Abu Bakar (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The dispersion of Muslim nation in Malaysia due to differences in political ideology which is named by the researcher as Political Partisan Dispersion is a pattern that exists till this day. This thesis is made to study the problem using the evaluation study in light of the Sunnah. It is made through defining its origin, phenomenon, causes and effects that arise in society and proposing a method to tackle the situation using prophetic revelation while conforming to the reality of the local politics in order to prevent the problem from growing or to reduce the impact of the dispersion hence solving it. This study uses the inductive, analytical and evaluation methods whereby the researcher gathers the theory on prophetic revelation and various interpretations of scholars and other Islamic resources that relate to dispersion, disagreement and Muslim unity. Theses, books and journals in the Malaysia political science field are also gathered to assess the Islamic political party in this country and the differences in its thoughts and ideology that contribute to the problem. Then the researcher produces the points that relate to the topic and analyses the revelation text and its interpretation to identify the opinions of the scholars on the meaning of the text. Later the opinions that relate to the Islamic political party in Malaysia are analyzed and the ideas are criticized. Finally, the researcher evaluates the points stated by the Sunnah in determining the dispersion concept, highlighting the political dispersion pattern and presenting the appropriate solutions for the research. This research has found that the phenomenon of this problem can be classified into four which are the accusation of other Muslims as disbelievers, disagreement on common issues, discrimination based on political ideology and excessive violence with those who have contradictory opinions. It has also discovered that the causes of the problems can be divided into four which are unhealthy political culture of Malaysia, the occurrence of false ideology and doctrine, the dismissal of Islamic rulings by certain politicians and dissimilarity of opinions on Islamic legislation on issues in confronting the government. Thus, this research has suggested five methods to tackle the problem which are eradicate political hegemony, prioritize religious loyalty more than political loyalty, treat the Malays as peaceful people to the religion, do not establish a new Islamic political party because it is expected to create dispersion and highlight the role of unbiased institutions.